2021
DOI: 10.5194/amt-14-239-2021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding balloon-borne frost point hygrometer measurements after contamination by mixed-phase clouds

Abstract: Abstract. Balloon-borne water vapour measurements in the upper troposphere and lower stratosphere (UTLS) by means of frost point hygrometers provide important information on air chemistry and climate. However, the risk of contamination from sublimating hydrometeors collected by the intake tube may render these measurements unusable, particularly after crossing low clouds containing supercooled droplets. A large set of (sub)tropical measurements during the 2016–2017 StratoClim balloon campaigns at the southern … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…The sensor module can be used to obtain temperature, RH, and air pressure, and it consists of three parts: (1) a negative temperature coefficient (NTC) thermistor sensor for temperature measurement that has an uncertainty of 0.8 K during rising stage and 2.8 K during flat-floating stage; (2) a piezoresistive sensor for air pressure measurement that has an uncertainty of 1 hPa during the rising stage and flat-floating stage; and (3) a humidity-sensitive capacitance sensor that has an uncertainty of 10 % RH during the rising stage but is ignored during flat-floating stage due to poor data quality. The uncontrolled, high-velocity descent via parachute during falling stage may influence the measure- ment quality due to a strong pendulum motion (Jorge et al, 2021); therefore, we do not consider the data from this stage.…”
Section: The Detection Principle and Quality Controlmentioning
confidence: 99%
“…The sensor module can be used to obtain temperature, RH, and air pressure, and it consists of three parts: (1) a negative temperature coefficient (NTC) thermistor sensor for temperature measurement that has an uncertainty of 0.8 K during rising stage and 2.8 K during flat-floating stage; (2) a piezoresistive sensor for air pressure measurement that has an uncertainty of 1 hPa during the rising stage and flat-floating stage; and (3) a humidity-sensitive capacitance sensor that has an uncertainty of 10 % RH during the rising stage but is ignored during flat-floating stage due to poor data quality. The uncontrolled, high-velocity descent via parachute during falling stage may influence the measure- ment quality due to a strong pendulum motion (Jorge et al, 2021); therefore, we do not consider the data from this stage.…”
Section: The Detection Principle and Quality Controlmentioning
confidence: 99%
“…Contamination due to outgassing from the balloon surface and cloud/rain droplets affects the dew/frost point measurements (Hall et al, 2016;Vömel et al, 2016;Jorge et al, 2021). Kräuchi et al (2016) showed an example of stratospheric contamination on an ascent profile starting from 25 km, with uncontaminated measurements above 27 km on the controlled descent measurement.…”
Section: Contamination By Outgassing From the Balloon Surface And Pay...mentioning
confidence: 99%